PENINGKATAN KAPASITAS KOMUNITAS PARIWISATA DESA TENTANG PARIWISATA KREATIF DI BELITUNG TIMUR - Ayu Krishna Yuliawati; Rofi Rofaida; Budhi Pamungkas Gautama; Shandra Rama Panji Wulung; Asti Nur Aryanti (LPPM Universitas Abdurrab, 2020)
The role of rural tourism development can help promote and help the local community of Sebunyuk Village. The purpose of this activity is to identify the needs and problems in developing Sebunyuk as a Tourism Village. The activity partner is the tourism community in Nam Pit Salu, Sebunyuk Village. The main problem is the mindset of people who still have a mindset as farm laborers or miners and do not see tourism as a field that benefits rural communities in the future. Partner problems are overcome through capacity building and assistance in implementing organization management, especially in management and marketing creative tourism products.